Computer-Mediated Discourse Analysis as Language Teaching Material: An Assessment of Exploration for Students Develop Democratic Character - Shaifullahh, AR (INVOTEC, 2018)
This exploratory study attempts to show the role of linguistic cross-disciplinary studies in the development of a democratic model of language learning in the context of Indonesian society post-reform. Using the case of interactive discourse in Internet as language teaching materials, analysis is conducted using grounded theory methods of text analysis. This study found that verbal signs reflect the equality relations between the media and the power of the responders in interactive discourse on the Internet. Such findings may be clues to the process of democratization in interactive discourse on the Internet. Therefore, this study recommends that interactive discourse on the Internet can be used as teaching materials in language learning in the classroom as part of efforts to build a democratic character of students.